Discrete structures and their interactions - Brown, Jason I. (Jason Ira), 1961- (Boca Raton : CRC Press/Taylor & Francis Group, 2013)
'Discover the Connections between Different Structures and Fields Discrete Structures and Their Interactions highlights the connections among various discrete structures, including graphs, directed graphs, hypergraphs, partial orders, finite topologies, and simplicial complexes. It also explores their relationships to classical areas of mathematics, such as linear and multilinear algebra, analysis, probability, logic, and topology.The text introduces a number of discrete structures, such as hypergraphs, finite topologies, preorders, simplicial complexes, and order ideals of monomials, that most graduate students in combinatorics, and even some researchers in the field, seldom experience. The author explains how these structures have important applications in many areas inside and outside of combinatorics. He also discusses how to recognize valuable research connections through the structures.Intended for graduate and upper-level undergraduate students in mathematics who have taken an initial course in discrete mathematics or graph theory, this book shows how discrete structures offer new insights into the classical fields of mathematics. It illustrates how to use discrete structures to represent the salient features and discover the underlying combinatorial principles of seemingly unrelated areas of mathematics'--
Discrete structures : a common framework -- Graphs and directed graphs -- Preorders and partial orders -- Hypergraphs -- Complexes and multicomplexes -- Research problems -- Set theory -- Matrix theory and linear algebra -- Abstract algebra -- Probability -- Topology -- Logic.
Includes bibliographical references and index.
Keywords: Graph theory -- Data processing; Combinatorial analysis; Computer algorithms